The challenges of proximity television in northern Chile: The case of the Coquimbo region - Carolina Alejandra Rodríguez Malebrán (2020)
Television Proximity are broadcast media called to support the access of information and enhancement to territories, wich seeks to represent to the local audience in their contents, rescue their identity and offsetting information dependency exercised by national networks. The present work aims, to analyze the challenges of television proximity, in the Region of Coquimbo, northern part of Chile. Analyze its structure, operation and content production system, especially in a particular context of technological transition that the country is going through. After a survey revealed, the number of channels were on air at the time of the investigation, a mixed methodology was used, consisting of a documentary analysis and interviews with the producers and content managers of each channel, six media belonging to the one hundred percent of the universe - and then a questionnaire was applied to the production staff television channels. Among the results, it stands out the television proximity stations operate with a minimum of human and financial resources. They have no a totally support or is unattainable for most channels. The lack off advertising funding prevents improving the quality of the content, as well as its frequency. Despite of these difficulties and the limited support of government public policies, these media are essential to protect the culture, local identity and put on the agenda issues and problems that would otherwise not be addressed by central authorities.